(untitled) (Fiep Bulletin - online, 2011)
This work aims to perform a reading of the movie Gattaca with the concept of Biopolitics developed by Michel Foucault. First we bring to the theoretical reflection, soon after, we made the film analysis. After analysis we concluded that the movie Gattaca shows the control made possible by biopolitics, but also the possibility of leakage of resistance existing in a society shaped by the monitoring and genetic control.